Initiating Maintenance Dialysis Before Living Kidney Donor Transplantation When a Donor Candidate Evaluation Is Well Underway. Issue 7 (July 2018) - Habbous, Steven; McArthur, Eric; Dixon, Stephanie N.; McKenzie, Susan; Garcia-Ochoa, Carlos; Lam, Ngan N.; Lentine, Krista L.; Dipchand, Christine; Litchfield, Kenneth; Begen, Mehmet A.; Sarma, Sisira; Garg, Amit X.
Abstract : Background: Preemptive kidney transplants result in better outcomes and patient experiences than transplantation after dialysis onset. It is unknown how often a person initiates maintenance dialysis before living kidney donor transplantation when their donor candidate evaluation is well underway. Methods: Using healthcare databases, we retrospectively studied 478 living donor kidney transplants from 2004 to 2014 across 5 transplant centers in Ontario, Canada, where the recipients were not receiving dialysis when their donor's evaluation was well underway. We also explored some factors associated with a higher likelihood of dialysis initiation before transplant. Results: A total of 167 (35%) of 478 persons with kidney failure initiated dialysis in a median of 9.7 months (25th-75th percentile, 5.4-18.7 months) after their donor candidate began their evaluation and received dialysis for a median of 8.8 months (3.6-16.9 months) before kidney transplantation. The total cohort's dialysis cost was CAD $8.1 million, and 44 (26%) of 167 recipients initiated their dialysis urgently in hospital. The median total donor evaluation time (time from evaluation start to donation) was 10.6 months (6.4-21.6 months) for preemptive transplants and 22.4 months (13.1-38.7 months) for donors whose recipients started dialysis before transplant. Recipients were more likely to start dialysis if their donor was female, nonwhite, lived in a lower-income neighborhood, and if the transplant center received the recipient referral later. Conclusion: One third of persons initiated dialysis before receiving their living kidney donor transplant, despite their donor's evaluation being well underway. Future studies should consider whether some of these events can be prevented by addressing inappropriate delays to improve patient outcomes and reduce healthcare costs. Abstract : This analysis using healthcare databases from 5 transplant centers in Canada confirms the difficulties in performing preemptive kidney transplants even with expedited living donor evaluation. Yet, not all the factors accounting for this observation can be promptly optimized. Supplemental digital content is available in the text.